IMF Research Bulletin, March 2002. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2002)
Articles reviewing IMF research on dollarization and on the relationship between macroeconomic policies and income distribution; country/area study: The Euro Area; summaries of Second Annual IMF Research Conference and Investor Relations Seminar; list of external publications of IMF staff; IMF working papers; visiting scholars at the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet